Pareto-improving bequest taxation - Volker Grossmann; Panu Poutvaara (Institute for the Study of Labor (IZA), 2006)
Altruistic parents may transfer resources to their offspring by providing education, and by leaving bequests. We show that in the presence of wage taxation, a small bequest tax may improve efficiency in an overlapping-generations framework with only intended bequests, by enhancing incentives of parents to invest in their children's education. This result holds even if the wage tax rate is held constant when introducing bequest taxation. We also calculate an optimal mix of wage and bequest taxes with alternative parameter combinations. In all cases, the optimal wage tax rate is clearly higher than the optimal bequest tax rate, but the latter is generally positive when the required government revenue in the economy is sufficiently high.
Keywords: 330; Erbschaftsteuer; Optimale Besteuerung; Bildungsinvestition; Privater Transfer; Lohnsteuer; Overlapping Generations; Pareto-Optimum; Theorie